We are now standing on not normal land: nurses' competency in disaster management - Aung, Khin Thandar; Ahayalimudin, Nurul ‘Ain; Abdul Rahman, Nurul 'Inayati (www.saspublisher.com, 2017)
Currently, the incidence of disasters is the biggest catastrophes that threaten people‟s livelihoods, health, and others welfare around the world. This situation provides the challenges for health care professionals, particularly nurses. As a result, there is a global need for all healthcare workers to be prepared and be competent in disaster management. The purpose of this paper is to describe how the roles of nurses in disaster management and how much competencies is needed. By searching the related data sources of CINAL plus, Google scholar and research gate, this paper will discusses the nurses' roles and experiences in disaster management, the reason why nurses need competencies in disaster management and how should we do to achieve the competencies of nurses in disaster management. When a disaster strikes, nurses are the ones who receive the most challenging tasks among the health care team because they are the first responders to be called upon. For that reason, the nurses should have positive characteristics and competencies to be an appropriate role model in disaster care.